Building a ‘toolkit’ for change: evaluation of horse owner behaviour and knowledge transfer in response to an educational campaign - Lightfoot, Katie Louise (2020)
Colic is the umbrella term used to describe clinical signs of pain in the horse. A common source of concern for horse owners, colic has been shown to be the most common reason for emergency veterinary attendance in the United Kingdom (UK). However, despite having primary responsibility for maintaining the health and welfare of their animals, research has shown that horse owner knowledge of colic is limited. In response to these findings the ‘REACT Now to Beat Colic’ campaign was launched in September 2016. Interventions of this type are widely used within human medicine to raise awareness of select issues and elicit a positive change in behaviour. Yet, despite the importance of behaviour change on improved health outcomes, the success or failure of an intervention is rarely investigated. This thesis aimed to evaluate horse owner behaviour and the transfer of knowledge in response to the ‘REACT’ campaign.